DESENTRALISASI PENDIDIKAN (Studi tentang Kebijakan Penganggaran Sektor Pendidikan di Kabupaten Sarmi Tahun 2010) - , Melkisedek Sabarofek, S.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Development policies established by governments sometimes can show the level of the development in the region. In fact, the policy has been made can not be implemented. In this case, it takes the education sector of District of Sarmi. Education policy made by government to address the education issues in the District of Sarmi has not been implemented. Therefore, education policies are not supported with adequate budgetary policy. Ironically, education is one of the Sarmi Government's policies which prioritized in regional development. It becomes the very complex problems of education in District of Sarmi. Based on the background described above, the research questions formulated in this study were: how budgetary policy in the education sector. This study aims to determine the Sarmi government's vision of education as a priority with the necessary budgetary support. Through qualitative research with various data collection techniques including observation and interviews with various informants from executive, legislative and other education stakeholders. The author concludes that the progress of education in the district is difficult to achieve. The results also showed that the budgetary policy which conducted by the local government and has been conducted without transparent and open mechanism. Top-down budget policy without involving the education and other education stakeholders. This caused by budget policy process which not in accordance with existing mechanisms, from village musrenbang and SKPD musrenbang levels. Secondly, the role and influence of Regents is crucial in this processes related to budget policy and finally, the quality of human resources on the official local government were still weak. This was caused by government officials of Department of Education incapable to carry out their duties and responsibilities. Eventually, these issues affect the progress of the education sector in the District of Sarmi. The impact was evident from the condition and progress of education in the location. Firstly, the advice and education infrastructure was lack and damaged, therefore, it become a limited support for the learning process. Secondly, the implemented curriculum development program. Thirdly, the procurement program of new teacher was also not implemented. Fourth, an additional budget allocation program for schools was not existed. Finally, since this program has not been implemented, then, the development of education was obstructed. It was caused by Sarmi local government budgets do not prioritize education, in other words, budgetary policies are not implemented to favor the education sector.